The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/ijd.14497
|View full text |Cite
|
Sign up to set email alerts
|

Melasma and thyroid disorders: a systematic review and meta‐analysis

Abstract: AbstractsBackground Thyroid hormones may play a key role in melasma; however, melasma link with thyroid disorders remains controversial.Objectives To compare the serum levels of thyroid-stimulating hormone (TSH), T4, T3, anti-thyroid peroxidase (anti-TPO), and antithyroglobulin between patients with melasma and control group using meta-analysis.Methods We screened 10 databanks and search engines, searched mesh and nonmesh terms. The identified evidences were reviewed and quality assessed using the Newcastle-Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Moreover, these differences were more severe among women with melasma. 19 Thyroid hormone act in hemoglobin synthesis in adults by affecting hematopoietic process, hypothyroidism results in anemia. Iron deficiency anemia which is quite common in Indian subcontinent should be clarified with specific clinical condition that results in iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these differences were more severe among women with melasma. 19 Thyroid hormone act in hemoglobin synthesis in adults by affecting hematopoietic process, hypothyroidism results in anemia. Iron deficiency anemia which is quite common in Indian subcontinent should be clarified with specific clinical condition that results in iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be caused by increased pituitary adrenocorticotropic hormone 2 . In addition, it has been reported that there is a relationship between melasma and thyroid autoimmunity 11,12 . In a previous study, Dogra et al 13 reported that 18.7% of patients with hypothyroid had melasma and 6.2% had periocular pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors include pregnancy, hormonal therapies (including oral contraceptives), phototoxic and anti-epileptic medications, intense sun exposure [67], and genetic predisposition [68,69]. Recent studies suggest that thyroid hormones may play a key role in melasma [70].…”
Section: Melasmamentioning
confidence: 99%